EFEKTIVITAS EKSTRAK Annona squamosa (L.), Averrhoa bilimbi (L.), DAN Tithonia diversifolia TERHADAP PENGHAMBATAN MAKAN LARVA Crocidolomia pavonana (F.) - Harlina Kusuma Tuti (Agrisia: Jurnal Ilmu-Ilmu Pertanian, 2020)
Cabbage farmers (Brassicaceae) generally use synthetic insecticides to controlling the pest Croccidolomia pavonana (F.) (Lepidoptera: Crambidae). However, the unwise use of synthetic insecticides has negative impacts such as the occurrence of resistance and resurgence of pests and chemical residues in agricultural products. One of alternative strategies that can be adopted to reduce the negative impact of synthetic insecticide use is by utilization of botanical insecticide. The aim of this research was to study the activities of extract Averrhoa bilimbi leaves, Annona squamosa seeds, and Tithonia diversifolia flowers on feeding inhibition C. pavonana larvae. Feeding inhibition effect of three plant extracts was assessed by choice and no choice methods. Extracts of A. squamosa and T. diversifolia resulted in low feeding inhibition effect both on choice and no choice methods.Key words:  Botanical insecticides, cabbage pest, Crocidolomia pavonana (F.), feeding inhibition